1966
DOI: 10.1063/1.1727537
|View full text |Cite
|
Sign up to set email alerts
|

Exact Quantum-Mechanical Calculation of a Collinear Collision of a Particle with a Harmonic Oscillator

Abstract: Exact quantum-mechanical calculations of the transition probabilities for the collinear collision of an atom with a diatomic molecule are performed. The diatomic molecule is treated as a harmonic oscillator. A range of interaction potentials from very hard to very soft are considered. It is found that for ``realistic'' interaction potentials the approximate calculations of Jackson and Mott are consistently high, even when the transition probabilities are low and good approximate results are expected. In some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
1

Year Published

1973
1973
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(117 citation statements)
references
References 11 publications
4
112
0
1
Order By: Relevance
“…III to the collinear, nonreactive, atom-diatom system given by Secrest and Johnson. 17 Their exact quantum mechanical results for the transition probabilities will be compared to those calculated with the Airy and Bessel uniform approximation. The Hamiltonian is the same as given by Eq.…”
Section: Application To a Nonreactive Systemmentioning
confidence: 99%
“…III to the collinear, nonreactive, atom-diatom system given by Secrest and Johnson. 17 Their exact quantum mechanical results for the transition probabilities will be compared to those calculated with the Airy and Bessel uniform approximation. The Hamiltonian is the same as given by Eq.…”
Section: Application To a Nonreactive Systemmentioning
confidence: 99%
“…[15][16][17][18][19] However, it has also been established for some time that perturbation theory can fail for highfrequency oscillators in gas-phase collisions. 20 More recent studies have found that the conventional perturbation theory approach 14 gives lifetimes that differ significantly from experimental measurements in both clusters 21 and liquids. 22,23 This has been attributed to the potential energy surfaces 23 and, more significantly, to the need to modify the conventional perturbation theory approach using quantum correction factors, [23][24][25][26] i.e., by choosing an appropriate q(T).…”
Section: ͑11͒mentioning
confidence: 99%
“…See Appendix A for details. Using the propagation method, we obtained approximately three-place accuracy in any probability (squared amplitude of a solution vector element) greater than w- 6 • We tested the accuracy of our solution vectors in two ways. First, a vector's probabilities should sum to 1; our sum values were always one to four decimal places.…”
Section: Methodsmentioning
confidence: 99%
“…The Hamiltonian JC for the collision of A striking B 2 is 6 : (4) where M=mA/(mA+2mB). of energy and length are fiw and one-half the classical ground state vibrational amplitude, respectively.…”
Section: Introductionmentioning
confidence: 99%